2019
DOI: 10.1002/jcp.29119
|View full text |Cite
|
Sign up to set email alerts
|

miR‐222 inhibits cardiac fibrosis in diabetic mice heart via regulating Wnt/β‐catenin‐mediated endothelium to mesenchymal transition

Abstract: miR-222 participates in many cardiovascular diseases, but its effect on cardiac remodeling induced by diabetes is unclear. This study evaluated the functional role of miR-222 in cardiac fibrosis in diabetic mice. Streptozotocin (STZ) was used to establish a type 1 diabetic mouse model. After 10 weeks of STZ injection, mice were intravenously injected with Ad-miR-222 to induce the overexpression of miR-222. miR-222 overexpression reduced cardiac fibrosis and improved cardiac function in diabetic mice. Mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…On the other hand, the anti-fibrotic role of miRNA-221/222 family has been confirmed, as their down-regulation was associated with heart failure ( Verjans et al, 2018 ). The interplay between Wnt and miR-222 in EndMT regulation has been recently suggested ( Wang et al, 2020 ); specifically, miR-222 is able to suppress the hyperglycemia-induced EndMT and inhibit cardiac fibrosis by negatively regulating the Wnt/β-catenin pathway in diabetic mice ( Wang et al, 2020 ). Lastly, a further protective effect versus EndMT is exerted through the notch pathway and involves miR-18a-5p ( Geng and Guan, 2017 ).…”
Section: Mirnas Regulation Of Dcm-associated Endmtmentioning
confidence: 99%
“…On the other hand, the anti-fibrotic role of miRNA-221/222 family has been confirmed, as their down-regulation was associated with heart failure ( Verjans et al, 2018 ). The interplay between Wnt and miR-222 in EndMT regulation has been recently suggested ( Wang et al, 2020 ); specifically, miR-222 is able to suppress the hyperglycemia-induced EndMT and inhibit cardiac fibrosis by negatively regulating the Wnt/β-catenin pathway in diabetic mice ( Wang et al, 2020 ). Lastly, a further protective effect versus EndMT is exerted through the notch pathway and involves miR-18a-5p ( Geng and Guan, 2017 ).…”
Section: Mirnas Regulation Of Dcm-associated Endmtmentioning
confidence: 99%
“…Myocardial hypertrophy and fibrosis are among the most representative changes in DCM [25,26]. In DCM, the dynamic balance between synthesis and deposition of the myocardial extracellular matrix is disturbed, and excessive deposition of collagen and an imbalance in the collagen ratio lead to cardiac remodeling [27][28][29]. BNP is among the most relevant molecular markers of cardiac hypertrophy [30], and the level of BNP increased in the DCM group.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac function can be improved by inhibiting EndMT (46). Multiple studies have found that attenuated EndMT can reduce cardiac fibrosis (11,20,(47)(48)(49)(50)(51). EndMT can also cause vascular endothelial dysfunction and serves an important role in the process of atherosclerosis (52,53) and pulmonary fibrosis (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%